When Drains and Gains Coincide: Migration and International Football Performance - Ruxanda Berlinschi; Jeroen Schokkaert; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
We analyze the effects of football player migration to foreign leagues on the perfirmance of their home country national teams. We provide a theoretical model predicting a positive effect of migration on international football perfirmance due to superior skills acquired by players choosing to migrate to foreign leagues. We test this prediction using recent cross country data on international football perfirmance. In order to accurately measure the effect of skill acquisitions by migrating players, we construct a weighted migration index that takes into account the quality of the foreign league and the division in which national team players are employed. We find strong and robust support for the prediction that migration of players to foreign leagues improves international football perfirmance of their home countries.
Keywords: J61; L83; 330; Migration; Muscle Drain; International Football Performance; Fußballsport; Internationale Arbeitsmobilität; Auswanderung; Qualifikation; Welt